2017
DOI: 10.3390/ijerph14050545
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of a Community Exercise and Nutrition Program for Older Adults: Texercise Select

Abstract: The wide-spread dissemination of evidence-based programs that can improve health outcomes among older populations often requires an understanding of factors influencing community adoption of such programs. One such program is Texercise Select, a community-based health promotion program previously shown to improve functional health, physical activity, nutritional habits and quality of the life among older adults. This paper assesses the cost-effectiveness of Texercise Select in the context of supportive environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Thus, an overall gain of $7876 is adjusted to $8178.07 in 2015 dollars using PHCEPI and $9001.91 in 2017 dollars using CPIMC. While the latest estimates of the cost per participant (n = 65) for the intervention was $229[ 33 ]. Thereby, there was an overall cost of $7009 (-$14885 +$7876), yet after adjusting to 2015 dollars the cost was $6706.93 (-$14885 + $8178.07) and $5883.09 (-$14885 + $9001.91) using 2017 CPIMC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an overall gain of $7876 is adjusted to $8178.07 in 2015 dollars using PHCEPI and $9001.91 in 2017 dollars using CPIMC. While the latest estimates of the cost per participant (n = 65) for the intervention was $229[ 33 ]. Thereby, there was an overall cost of $7009 (-$14885 +$7876), yet after adjusting to 2015 dollars the cost was $6706.93 (-$14885 + $8178.07) and $5883.09 (-$14885 + $9001.91) using 2017 CPIMC.…”
Section: Resultsmentioning
confidence: 99%
“…In the results section, we report both cost estimates using the 2015 PHCEPI and 2017 CPIMC. Further, the medical cost is also compared to the relative program cost, estimated to be $229 per participant using multiple measures (e.g., estimated time volunteered for facilitators, supplies), with more detail reported elsewhere[ 33 ].…”
Section: Methodsmentioning
confidence: 99%
“…While there are many community-based evidence-based programs for older adults, less is known about the cost-effectiveness of these programs relative to other intervention strategies. Evidence is emerging for the cost-effectiveness of lifestyle programs that are designed to improve physical activity and dietary behaviors [ 28 ].…”
Section: Editorialmentioning
confidence: 99%
“…Over the past decades, the evidence-based movement has produced an abundant literature about the development, implementation, and evaluation of an array of evidence-based health and wellness programs serving community-dwelling older adults ( Birkel et al, 2014 ; Boutaugh & Lawrence, 2014 ; Ory & Smith, 2015 ). Building on research- and practice-based evidence, evidence-based programs have been shown to improve health of participants and benefit society by promoting efficient utilization of limited resources and reducing health care costs ( Ahn et al, 2013 ; Akanni, Smith, & Ory, 2017 ; Carande-Kulis, Stevens, Florence, Beattie, & Arias, 2015 ; Ory et al, 2013 ). The small group format, which is most commonly offered in community settings for older adults ( Smith et al, 2017 ; Smith, Ory, Belza, & Altpeter, 2012 ), has shown to have a growing reach throughout the United States, reaching vulnerable populations (e.g., rural and/or underserved populations with limited access to care) ( Smith et al, 2017 ; Towne et al, 2014a ; Towne, Smith, Ahn, & Ory, 2014b ).…”
Section: Introductionmentioning
confidence: 99%